A Leader Doesn't Sound Lesbian!: The Impact of Sexual Orientation Vocal Cues on Heterosexual Persons' First Impression and Hiring Decision. (June 2020) - Fasoli, Fabio; Hegarty, Peter
In three studies ( N = 340), we tested whether vocal cues to a person's sexual orientation prompted sexual orientation discrimination in heterosexual individuals when hiring leaders. Our results inform how gender and sexual orientation intersect to produce discriminatory effects in the hiring context. Heterosexual participants listened to short clips of voices that sounded like job candidate was a lesbian or heterosexual woman, or a gay or heterosexual man, and rated all for job suitability and employability. Candidates applied for jobs as leaders (Study 1), as leaders or assistants (Study 2), and for leadership roles that varied in both gender role and status (Study 3). Sexual orientation discrimination occurred in all three studies and was greater among women job candidates. Refuting role congruity theory, several findings disconfirmed the prediction that lesbian-sounding women would be advantaged when stereotyped as masculine and when applying for leadership roles. Rather, in line with status-beliefs theory, lesbian-sounding women and gay-sounding men were rated and ranked poorly to the extent that they were perceived as less competent than heterosexual candidates. Findings suggest that hiring discrimination occurs in subtle ways, such as when individuals sound gay/lesbian. This has implications for recruitment as well as sexual-orientation discrimination court cases. Online slides for instructors who want to use this article for teaching are available on PWQ 's website athttp://journals.sagepub.com/doi/suppl/10.1177/0361684319891168